Dimensions of Multicultural Education and Their Implications for Primary School Foreign Language Teaching - Werona Król (Multidisciplinary Journal of School Education, 2019)
In the context of contemporary reality, the issue of multicultural education is becoming more and more popular. Therefore, the purpose of the article is two-fold: to discuss Banks’ vve dimensions of multicultural education and to share some ideas on how these dimensions are or can be used to assist teachers in integrating multicultural content into their primary foreign language classrooms. Moreover, one section of the paper is devoted to the vgure of Professor James. A Banks, who is widely regarded as a founder of multicultural education. Moreover, the professor’s own rewections on the dimensions of interest expressed in the interview conducted by Tucker in 1998 are presented. Finally, having recognised the importance of early multicultural education, the author of the article concludes that primary foreign language teachers should not hesitate and encourages them to start preparing their students to become unbiased global citizens.